Peer Social Relationship on Students - Wiwin Andriani; Neviyarni S; Afdal Afdal (Indonesian Institute for Counseling, Education and Theraphy, 2020)
This research was conducted starting from the results of BK instrumentation applications, namely General AUM in semester 1 students majoring in curriculum and educational technology in the faculty of education at Padang State University which showed that students experienced problems in the field of social relations. This study uses quantitative methods to determine the social relations of peers to students majoring in curriculum and educational technology at the UNP FIP.